OPTIMIZATION OF MEMORIZATION IN TAHFIDZ EDUCATIONAL INSTITUTIONS: CHALLENGES AND STRATEGIES FOR ACHIEVE MEMORIZATION TARGET IN TAHFIDZUL QUR'AN EDUCATIONAL INSTITUTIONS - Natasabila, Adinda Dafina; Ilmi, Ahadiyah Lailatul; Fikriyah, Anisulil; Nadia, Nabila Nur Halimatus; Maqfiroh, Nuril Hasinatul; Masruroh, Yeni Dwi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Optimizing memorization of the Al-Qur'an in tahfidz educational institutions is a challenge in itself amidst current developments and various social dynamics. This research aims to identify the challenges faced by tahfidz institutions in achieving students' memorization targets and the strategies implemented to overcome them. A qualitative approach was used with the case study method at tahfidzul Qur'an educational institutions in Indonesia. The research results show that the main challenges include low student consistency, lack of parental involvement, and less than optimal teaching methods applied. The proposed strategies include strengthening time management, implementing technology-based tahfidz methods, intensive involvement of parents, and developing motivational programs based on spiritual values. By optimizing this strategy, Tahfidz institutions are expected to be able to improve the quality of students' memorization in a sustainable manner.